Validity and Reliability of Behavior and Theory-Based Psychosocial Determinants Measures, Using Audience Response System Technology in Urban Upper-Elementary Schoolchildren - Gray, Heewon Lee (ELSEVIER SCIENCE INC, 2023)
10.1016/j.jneb.2016.03.018